2008
DOI: 10.1037/a0012682
|View full text |Cite
|
Sign up to set email alerts
|

Developmental change in the acuity of the "number sense": The approximate number system in 3-, 4-, 5-, and 6-year-olds and adults.

Abstract: Behavioral, neuropsychological, and brain imaging research points to a dedicated system for processing number that is shared across development and across species. This foundational Approximate Number System (ANS) operates over multiple modalities, forming representations of the number of objects, sounds, or events in a scene. This system is imprecise and hence differs from exact counting. Evidence suggests that the resolution of the ANS, as specified by a Weber fraction, increases with age such that adults ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

65
656
2
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 791 publications
(727 citation statements)
references
References 64 publications
65
656
2
4
Order By: Relevance
“…Most other cognitive abilities, with the notable exception of face recognition ability (29), appear to peak earlier. This extends previous studies, which suggested developmental changes in w in smaller laboratory-based samples (9,10). The large overlap among interdecile ranges across the lifespan (Fig.…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…Most other cognitive abilities, with the notable exception of face recognition ability (29), appear to peak earlier. This extends previous studies, which suggested developmental changes in w in smaller laboratory-based samples (9,10). The large overlap among interdecile ranges across the lifespan (Fig.…”
Section: Resultssupporting
confidence: 77%
“…Here we investigated change in the approximate number system (ANS), the cognitive system that gives rise to our basic numerical intuitions (3). The ANS generates nonverbal representations of numerosity in nonhuman animals (4,5), infants (6, 7), school-aged children (8)(9)(10), and adults from mathematically fluent cultures (11,12) as well as cultures that do not practice explicit mathematics (13,14). In humans, imaging results suggest that these basic intuitions are supported by neurons in the intraparietal sulcus (15)(16)(17)(18), a role that can be observed shortly after birth (19).…”
mentioning
confidence: 59%
“…Studies using psychophysical techniques to quantify the coarseness of nonsymbolic number representations point to large individual differences in precision throughout the lifespan (21,22). Whereas some people have more noise associated with the ANS (i.e., more overlap in the Gaussian curves), others have less noise (i.e., less overlap in the Gaussian curves).…”
mentioning
confidence: 99%
“…Additional evidence for a link between the ANS and symbolic arithmetic comes from individuals with dyscalculia, known as a specific disability in learning school-relevant math (17). Recent studies suggest that dyscalculia is also characterized by deficits in ANS processing such as nonsymbolic number comparison (18), with atypical IPS activation during both symbolic arithmetic (19) and approximate nonsymbolic comparisons (20).Studies using psychophysical techniques to quantify the coarseness of nonsymbolic number representations point to large individual differences in precision throughout the lifespan (21,22). Whereas some people have more noise associated with the ANS (i.e., more overlap in the Gaussian curves), others have less noise (i.e., less overlap in the Gaussian curves).…”
mentioning
confidence: 99%
“…In general, children and adults are fairly accurate in comparing the approximate sizes of numerical magnitudes (Booth & Siegler, 2006;Halberda & Feigenson, 2008;McCrink & Wynn, 2004). Understanding of counting procedures develops later (Opfer & Siegler, 2012).…”
Section: Processing Strategies For Quantitative Reasoningmentioning
confidence: 99%